The Study of Social and Cultures' Society at Koto Panjang Reservoir Catchment Area in the Lima Puluh Kota and Kampar District - Khairani,; Dewata, Indang (International Journal of Psychosocial Rehabilitation, 2020)
The construction in Koto Panjang reservoir catchment area Lima puluh Kota and Kampar district is caused by the land use change that continues to occur due to changes in the social and cultural conditions of the community, not only as a supplier of electricity in Sumatra's interconnection but also causing floods. Therefore, the aim of the research is to study social conditions and culture after the construction of the Koto Panjang reservoir catchment area in Lima Puluh Kota and Kampar districts. The type of this research is qualitative,, with data collection techniques using questionnaires, observation, interviews, and documentation. Furthermore, the data obtained were analyzed descriptively by using percentages to describe the social and cultural conditions of communities in the study area. The results showed that the forests exist around the Koto Panjang reservoir catchment area in a customary land society where the participation of traditional leaders in the management of forest areas is still low, as seen from the absence of the customary rules (values/norms) that restrict the activities of people in the forest so that people can perform economic activities through farming and agriculture freely. Agriculture and farming activities to improve the local economic effect on floods and landslides.